Supplement of bamboo extract lowers serum monocyte chemoattractant protein-1 concentration in mice fed a diet containing a high level of saturated fat - Higa, Jason K.; Liu, Wanyu; Berry, Marla J.; Panee, Jun (British journal of nutrition, 2011)
Monocyte chemoattractant protein-1 (MCP-1) is an inflammatory chemokine up-regulated in obese subjects, contributing to the development of type 2 diabetes. The present study investigated the inhibitory effect of an ethanol–water extract from bamboo (BEX, Phyllostachys edulis) on the blood concentration of MCP-1. C57BL/6J mice were fed a standard diet or a high-fat diet with or without the BEX supplement (11 g dry mass/17 000 kJ) for 6 months. A total of ten mice were used in each group. Body weight and food consumption were measured weekly. After euthanisation, the weight of visceral fat and circulating MCP-1 concentration were measured. In comparison with the standard control group, the high-fat control group had increased body weight, abdominal fat storage and serum MCP-1 concentration by 60 % (P < 0·001), 266 % (P < 0·001) and 180 % (P < 0·01), respectively. In comparison with the high-fat control group, the high-fat BEX group showed a 3 % decrease in body weight (P < 0·01), 24 % decrease in mesenteric fat depot (P < 0·01) and 49 % decrease in serum MCP-1 concentration (P < 0·05). The present study suggests that the BEX supplement in the high-fat diet ameliorates elevated MCP-1 concentrations in the blood, and whether this is related to modulated endocrine properties of the visceral fat is to be studied.